Genesis, Gender, and Human Identity: A Theological and Philosophical Exploration - Goshu, Belay Sitotaw; Ridwan, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This study investigates the intersection of biblical interpretations, philosophical thought, and gender theory to explore how the concept of human identity and gender roles has evolved. The purpose of this research is to analyze traditional religious and philosophical views on gender duality, focusing on interpretations of the Genesis creation narrative and philosophical ideas like Plato’s Symposium. Methodologically, the study adopts a qualitative approach, incorporating theological, historical, and logical analysis to assess various interpretations of gender identity. The findings reveal that while traditional religious perspectives emphasize gender complementarity, philosophical discourses present androgyny as a model for understanding human identity. This research highlights the need for a contemporary dialogue between theological institutions and modern gender theory to address issues of gender equality and identity formation. The conclusion recommends that religious institutions reconsider their stances on gender roles and engage with evolving social perspectives to promote a more inclusive view of human identity. Ultimately, the study advocates for inclusive theological reflection that respects traditional values and modern understandings of gender equality.